2017
DOI: 10.1186/s12711-017-0319-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the genetic architecture and improving genomic prediction accuracy for mastitis and milk production traits in dairy cattle by mapping variants to hepatic transcriptomic regions responsive to intra-mammary infection

Abstract: BackgroundA better understanding of the genetic architecture of complex traits can contribute to improve genomic prediction. We hypothesized that genomic variants associated with mastitis and milk production traits in dairy cattle are enriched in hepatic transcriptomic regions that are responsive to intra-mammary infection (IMI). Genomic markers [e.g. single nucleotide polymorphisms (SNPs)] from those regions, if included, may improve the predictive ability of a genomic model.ResultsWe applied a genomic featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 62 publications
2
49
0
Order By: Relevance
“…features. If few (or even no) causal variants are contained in the genomic feature, the accuracy of GFBLUP will decrease because of too much weight being given to spurious genomic features (Fang et al, 2017). Similar results were also found in this study (Table 2).…”
Section: Genomic Feature Blup Model For Genomic Predictionsupporting
confidence: 88%
“…features. If few (or even no) causal variants are contained in the genomic feature, the accuracy of GFBLUP will decrease because of too much weight being given to spurious genomic features (Fang et al, 2017). Similar results were also found in this study (Table 2).…”
Section: Genomic Feature Blup Model For Genomic Predictionsupporting
confidence: 88%
“…grouping genetic variants into functional pathways, can increase the prediction accuracy markedly. [33][34][35][36][37][38] Therefore, we investigated if similar benefits could be achieved by partitioning the metabolome.…”
Section: Nmr Cluster-guided Phenotypic Predictionsmentioning
confidence: 99%
“…Gene ontology (GO) terms are a useful resource of groups of genes with shared biological, molecular or cellular functions (The Gene Ontology Consortium 2000). An extension of the standard genomic best linear unbiased prediction (GBLUP, Meuwissen et al (2001)), which allows the addition of an extra genetic component for a set of genetic markers, e.g., all those within a certain GO term, is genomic feature best linear unbiased prediction (GFBLUP, Edwards et al (2015, 2016; Ehsani et al (2015); Sarup et al (2016);Fang et al (2017)). The genomic feature model is described below, along with a method to decompose the genetic variance within a GO term to the variance explained per gene within GO term.…”
Section: Identification Of Predictive Snp Setsmentioning
confidence: 99%
“…Previous work has demonstrated that prediction models incorporating prior biological information enriched for causal variants can increase the predictive ability of complex traits (Edwards et al 2016;Sarup et al 2016;Fang et al 2017). Recently it was shown in the DGRP that the level of predictive ability of complex traits depends on the underlying genetic architecture (Edwards et al 2016).…”
Section: Determining the Genotype-phenotype Mapmentioning
confidence: 99%
See 1 more Smart Citation